Basal insulin persistence, associated factors, and outcomes after treatment initiation among people with type 2 diabetes mellitus in the US. (2nd April 2016) - Perez-Nieves, Magaly; Kabul, Samaneh; Desai, Urvi; Ivanova, Jasmina I.; Kirson, Noam Y.; Cummings, Alice Kate; Birnbaum, Howard G.; Duan, Ran; Cao, Dachuang; Hadjiyianni, Irene
Abstract: Objective To assess basal insulin persistence, associated factors, and economic outcomes for insulin-naïve people with type 2 diabetes mellitus (T2DM) in the US. Research design and methods People aged ≥18 years diagnosed with T2DM initiating basal insulin between April 2006 and March 2012 (index date), no prior insulin use, and continuous insurance coverage for 6 months before (baseline) and 24 months after index date (follow-up period) were selected using de-identified administrative claims data in the US. Based on whether there were ≥30 day gaps in basal insulin use in the first year post-index, patients were classified as continuers (no gap), interrupters (≥1 prescription after gap), and discontinuers (no prescription after gap). Main outcome measures Factors associated with persistence – assessed using multinomial logistic regression model; annual healthcare resource use and costs during follow-up period – compared separately between continuers and interrupters, and continuers and discontinuers. Results Of the 19, 110 people included in the sample (mean age: 59 years, ∼60% male), 20% continued to use basal insulin, 62% had ≥1 interruption, and 18% discontinued therapy in the year after initiation. Older age, multiple antihyperglycemic drug use, and injectable antihyperglycemic use during baseline were associated with significantly higher likelihoods of continuing basal insulin. Relative to interrupters and discontinuers, continuers had fewer emergency department visits, shorter hospital stays, and lower medical costs (continuers: $10, 890, interrupters: $13, 674, discontinuers: $13, 021), but higher pharmacy costs (continuers: $7449, interrupters: $5239, discontinuers: $4857) in the first year post-index ( p  < 0.05 for all comparisons). Total healthcare costs were similar across the three cohorts. Findings for the second year post-index were similar. Conclusions The majority of people in this study interrupted or discontinued basal insulin treatment in the year after initiation; and incurred higher medical resource use and costs than continuers. The findings are limited to the commercially insured population in the US. In addition, persistence patterns were assessed using administrative claims as opposed to actual medication-taking behavior and did not account for measures of glycemic control. Further research is needed to understand the reasons behind basal insulin persistence and the implications thereof, to help clinicians manage care for T2DM more effectively.